Efficacy and Safety of Traditional Chinese Herbal Medicine for Antipsychotic-Related Constipation: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Rao, Wen-Wang; Yang, Juan-Juan; Qi, Han; Sha, Sha; Zheng, Wei; Zhang, Ling; Ungvari, Gabor S.; Ng, Chee H.; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Abstract Background: Constipation is a common but often ignored side effect caused by antipsychotic treatment, although it is associated with adverse outcomes. The results of the efficacy and safety of traditional Chinese herbal medicine (TCM) in treating constipation are mixed across studies. This is a systematic review and meta-analysis of randomized controlled trials (RCTs) of the efficacy and safety of TCM compared to Western medicine (WM) in treating antipsychotic-related constipation. Methods: Major international electronic (PubMed, EMBASE, Cochrane Library and Web of Science) and Chinese (Wanfang, WeiPu VIP, SinoMed and CNKI) databases were searched from their inception to November 29, 2020. Meta-analysis was performed using the random-effects model. Results: Thirty RCTs with 52 arms covering 2,570 patients in the TCM group and 2,511 patients in the WM group were included. Compared with WM, TCM alone was superior regarding the moderate response rate [Risk Ratio (RR) =1.165; 95% confidence interval (CI), 1.096-1.238; P<0.001], marked response rate (RR=1.437; 95% CI, 1.267-1.692; P<0.001) and remission rate (RR=1.376; 95% CI, 1.180-1.606; P<0.001) for constipation, while it was significantly associated with lower risk of rash (RR=0.081; 95% CI, 0.019-0.342; P=0.001). For the moderate response rate, meta-regression analyses revealed that publication year (β=-0.007, P =0.0007) and Jadad score (β=0.067, P<0.001) significantly moderated the results. For the remission rate, subgroup and meta-regression analyses revealed that the geographical region (P=0.003), inpatient status (P=0.035) and trial duration (β=0.009, P=0.013) significantly moderated the results. Conclusions: The efficacy of TCM for antipsychotic-related constipation appeared to be greater compared to WM, while certain side effects of TCM, such as rash, were less frequent.